Improving The Organizational Performance Through Work Motivation, Satisfaction and Productivity - Hasbiyadi Hasbiyadi (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
The theme of this research is organizational performance: job motivation, job satisfaction and productivity. A sample of 64 employees uses random sampling to collect data. This study uses questionnaires to collect data and provides direct questionnaires to respondents. The data analysis technology in this study uses SmartPLS 3 analysis tools for path analysis. The results show that there is a positive correlation between job satisfaction and organizational performance, and there is also a positive correlation between job satisfaction and productivity. Path analysis found that motivation and job satisfaction had no effect on organizational performance. Therefore, it can be concluded that productivity is not an intervention variable between job satisfaction motivation.